STRUKTUR BIAYA DAN PENENTUAN HARGA ANGKUT TBS KELAPA SAWIT OLEH KONTRAKTOR - tri endar suswatiningsih (Universitas Muhammadiyah Purwokerto, 2021)
Transporting Fresh Fruit Bunches (FFB) is an important activity in oil palm plantation companies. The FFB that is harvested, must be transported to the mill on the same day. The contractor is one of the parties who collaborates in transporting FFB. This study examined the structure of the cost of transporting FFB by contractors, determining the transport price and the benefits obtained. This research was a case study at PT SINP (Surya Indah Nusantara Pagi) Pangkut Village, Arut Utara District, Kotawaringin Barat District, Central Kalimantan Province. There were 7 contractors working together in transporting FFB. The economic analysis includes fixed costs and variable costs, as well as determined the transportation price based on the distance to the palm oil millThe results showed that the structure of the transportation costs incurred by the contractor consists of fixed costs (depreciation costs, capital interest costs, maintenance costs and vehicle taxes) while the variable costs include fuel costs, driver fees, FFB loading and unloading fees, and income tax costs. The cost of transportation for FFB contractors transporting FFB from afdeling close to PKS was IDR 20.09 / kg, and those far from the palm oil mill was IDR 31.75 / kg. The contractor's profit was higher if it transports FFB from afdeling closer to the palm oil mill